2019
DOI: 10.5371/hp.2019.31.4.224
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiological Outcomes of Rectangular Tapered Cementless Stem According to Proximal Femoral Geometry in Elderly Asian Patients

Abstract: Purpose: A retrospective analysis of mid-to long-term clinical and radiological outcomes of Korean patients over 60 years of age who underwent hip arthroplasty using a cementless rectangular tapered stem according to Dorr proximal femur geography. patients (112 hips) underwent hip arthroplasty using the C2 stem. The mean age of patients was 77.4 years (range, 60-91 years) and the mean follow-up duration was 91.1 months (range, 60-116 months). All patients were evaluated clinically and radiologically with speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…A C2 stem (Lima Corporate SpA, Udine, Italy) was used in our previous study; the results showed more frequent occurrence of RLL and thigh pain in patients with Dorr type A 18) . The design of the C2 stem is similar to that of the COREN stem; a rectangular tapered stem with proximal fitting.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A C2 stem (Lima Corporate SpA, Udine, Italy) was used in our previous study; the results showed more frequent occurrence of RLL and thigh pain in patients with Dorr type A 18) . The design of the C2 stem is similar to that of the COREN stem; a rectangular tapered stem with proximal fitting.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, relief of thigh pain was achieved within two years after surgery without complications in all patients. Although the cause of the pain relief may be uncertain, previous studies reported that relief of thigh pain was achieved with time 8 18) .…”
Section: Discussionmentioning
confidence: 99%
“…Kang et al performed hip arthroplasty using a type 3C stem and reported radiological results after more than five years [32]. Of the 112 cases followed up, 15 cases (13.4%) showed a radiolucent line, and there were significant cases of lack of calcar filling (p = 0.033), which may occur when the calcar fill is insufficient, as the proximal femoral region is wide in the case of a Dorr A type femur.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 112 cases followed up, 15 cases (13.4%) showed a radiolucent line, and there were significant cases of lack of calcar filling (p = 0.033), which may occur when the calcar fill is insufficient, as the proximal femoral region is wide in the case of a Dorr A type femur. The fine motion of the femoral stem causes bone resorption, and the fibrous membrane fills the gap between the femoral stem and inner cortex, which appears radiolucent on plain radiography [32]. Furthermore, Lutz et al, performed hip arthroplasty using a type 3C stem and analyzed the clinical and radiological outcomes determined by CT-assisted osteodensitometry of bone mineral density and bone mineral changes of the femoral cortical and cancellous bone [33].…”
Section: Discussionmentioning
confidence: 99%